Reproductive donation practice, policy, and bioethics - Richards, Martin 1940 January 26-; Pennings, Guido; Appleby, John 1984- (Cambridge University Press, 2012)
Reproductive donation is the most contentious area of assisted reproduction. Even within Europe there are wide variations in what is permitted in each country. This multidisciplinary book takes a fresh look at the practices of egg, sperm and embryo donation and surrogacy, bringing together ethical analysis and empirical research. New evidence is offered on aspects of assisted reproduction and the families these create, including non-traditional types. One of the key issues addressed is should children be told of their donor origin? If they do learn the identity of their donor, what kinds of relationships may be forged between families, the donor and other donor sibling families? Should donation involve a gift relationship? Is intra-familial donation too close for comfort? How should we understand the growing trend for 'reproductive tourism'? This lively and informed discussion offers new insights into reproductive donation and the resulting donor families